Cytomegalovirus DNA detection in pregnant women with a high IgG avidity index: a valuable tool for diagnosing non-primary infections?. (12th December 2022) - Karageorgou, Ioulia; Kossyvakis, Athanasios; Jiménez, Juan; Garcia, Irene; Mentis, Alexios-Fotios A.
Abstract: Background/Aim: Congenital human cytomegalovirus infection (cCMV) is the commonest congenital infection, and it can result in hearing loss and neurodevelopmental delay. Even if primary infections are more frequent and cause more severe congenital cCMV manifestations compared to NPIs, and despite partial protection from maternal immunity, the highest birth prevalence of cCMV is observed in seropositive women with non-primary CMV infection (NPI). Given that NPI contribute significantly to the overall burden of cCMV, their accurate diagnosis of NPI remains clinically important. Considering that the serological testing for CMV infection is not always reliable, we sought to determine whether detection of CMV DNA in pregnant women with a high IgG avidity index (AI) can help diagnose NPI. Materials and methods: Human CMV serology screening (IgG, IgM, and IgG AI) was performed for confirmation of CMV infection in serum samples from mainly pregnant women with indications of CMV infection due to IgG + and IgM + -positive samples in other laboratories. Pregnant women (or those with termination of pregnancy during the last period) with adequate IgG levels to perform IgG AI were included. Demographic data and mean gestation week at the time of screening were recorded. Serological testing was performed using CE-IVD commercial kits. CMV DNAemia detection by real time PCR (RT-PCR) was applied to confirm suspected CMV infection. Results: Nine-hundred and thirty-four pregnant women CMV IgG positive with adequate IgG titers for AI testing were included in the study. The percentage of women with a high AI was 71.8% (671/934); among them, nearly 2.4% (16/671) had presence of CMV DNA. Also, 12.4% of women (116/934) had intermediate IgG AI and 15.7% of women (147/934) had low IgG AI. The presence of CMV DNA was observed in 13.8% (16/116) and 39.5% (58/147) of the groups with intermediate and low IgG AI, respectively. A high CMV IgG AI was associated with a negative CMV PCR status ( p -value <.00001). Conclusions: CMV DNA was present in 2.4% of seropositive women with high IgG AI, indicating active NPI and thus, harboring the risk of cCMV sequelae to the fetus. Moreover, the incidence of NPI may have been underestimated due to single timepoint testing. In order to detect CMV NPI in a seropositive woman, regular and frequent serology testing as well as detection of CMV DNAemia are required which render the whole diagnostic process impractical and not cost-effective.